Critical thinking, curriculum mapping, and economic education: an essay. (24th December 2021) - Friesner, Daniel; Hackney, Donald D.
This essay argues that the economics profession must better define what critical thinking is, how it is embedded in our teaching, and how that teaching incorporates both the breadth and depth with which those topics are covered. Doing so will allow economists to: 1) identify and remediate gaps in the depth or breadth of students' critical thinking skills as they are used in economics; 2) more effectively convey economic concepts to students in the classroom; 3) promote greater understanding and appreciation for different schools of economic thought.